THE PRAISE OF PROSE IN ACHIEVING PARTICIPATORY ENGLISH LANGUAGE TEACHING (ELT) - Al-Hafizh, Muhammad (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2010)
There were great shifts in English Language Teaching (ELT) approaches and methodologies in recent years. At the same time, many researches occurred about the applications of teaching English as Second Language (ESL). It shows that, changes and innovations are something good in order to find a better pedagogic system and to be more professional in ELT. Sometimes, people resist new ways of looking, at least at the first, and it happened on ELT as well. This article is aimed at revealing ELT new ways of looking-to consider the beneficial factors of using prose in enriching interactive English language teaching into participatory English language teaching, whenever teacher and students are able to share power and come together in dialogue and mutual respect. It is considerable to reach the two components of English language pedagogy; cognitive abilities, and proficiency in English language. The writer is inspired by the thought of Shirley Brice Heath once said that â€œliterature has no rival in its power to create natural repetition, reflection on language and how it works, and attention to audience response on the part of learnersâ€. Teachers can use prose as a pivot in literature-based curriculum, around which curriculum revolves. In this article there will be five praiseworthy elements of prose as a pivot of participatory ELT that are going to be discussed; (1) prose is authentic, (2) prose can provide memorable contexts for the language, (3) prose illustrates appropriate language for specific situations, (4) prose links students to other cultures and subcultures, (5) prose presents topics for critical analysis, discussion, writing, and encourages performance.